The Challenge of Adapting the Rule of Law to Technological Developments - Rusdiana, Emmilia (Jurnal Idea Hukum, 2024)
The problem in the digital era is that technology is developing rapidly without being accompanied by sufficient legal rules.  Meanwhile, laws and regulations are always lagging and cannot achieve legal flexibility in society. One of the results of technological development is electronic sports matches. This research reviews the concept of cyber law and the development of information and technology, especially in dealing with electronic matches. This article aims to validate the legal concept of adjusting to the rules of law in the electronic field that applies in Indonesia. The research method is juridical normative with a legislative and conceptual approach starting from the origin of ideas and doctrines developed into a legal study.   First, is threat of e-sports offences. e-sports offences including sexual harassment, gender, and drugs can be addressed by the applicable regulations, namely the Electronic Information and Transaction Law. When there are developments in information and technology, these can be based on "unwritten" rules or laws that apply in society.  Secondly,  the gambling industry has the opportunity to influence the sustainability of e-sports competitions. An indication of corruption in e-sports competitions can be bribery, and this requires law enforcement with the Information and Electronic Transactions Law or also by using unwritten rules.